Gross efficiency during flat cycling in laboratory and field conditions - Nimmerichter, A.; Haselberger, K.; Prinz, B. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Gross efficiency (GE) is described as the ratio of mechanical work accomplished to the metabolic energy required to do that work and is considered as important determinant of cycling performance. Only a few studies examined GE in field conditions and Bertucciet al. (2012) reported GE to be 10% lower in laboratory compared to field conditions when cycling at freely chosen cadences. Previously it was shown, that cadence (60 vs. 90 rpm) and terrain (flat vs. uphill) affect GE in field conditions (Nimmerichter et al. 2015). The aim of this study was to compare GE at controlled power output and cadence during laboratory and field cycling. Methods: Thirteen trained cyclists (mean ± SD: age 24 ± 5 years; stature 177.4 ± 6.3 cm; body mass 67.6 ± 7.8 kg) performed an incremental ergometer test to determine maximal power (402 ± 39 W), VO2max (68.3 ± 4.2 mL/min/kg) and the first ventilatory threshold (VT: 180 ± 19 W). On two separate days the participants performed two trials of 6-min in a seated position on level ground cycling (1.5%) at 90 rpm at an exercise intensity of 90%VT (162 ± 20 W) in laboratory and field conditions. Power output was measured with an SRM professional power crank. To simulate the gradient in laboratory conditions, the bicycle was mounted on an indoor trainer (TACX Elite) and was fixed on a treadmill. Oxygen uptake was measured breath-by-breath with a portable gas analyser (MetaMax3B, CORTEX). Gross efficiency was calculated as GE (%) = work rate/energy expenditure*100. Energy expenditure was calculated using the formula of Brouwer (1957). Paired samples t-tests were used to compare GE, VO2 and power output between laboratory and field cycling. The level of significance was set at p < 0.05. Results: There were no significant differences between laboratory and field conditions for power output (163 ± 21 W vs. 167 ± 22 W; t12 = 1.88; p =0.09), GE (18.6 ± 1.2% vs. 18.8 ± 1.9%; t12 = 0.29; p = 0.77) and VO2 (2.54 ± 0.37 L/min vs. 2.61 ± 0.43L/min; t12 = 1.41; p = 0.25). Discussion: As both, power output and cadence affect GE, the results of the present study indicate the importance to control these variables to determine GE in laboratory and field conditions. In contrast to a previous study were significant differences were reported at freely chosen cadences (Bertucci et al. 2012), this was not found under controlled conditions. Although effects of terrain on GE were reported in a previous study (Nimmerichter et al. 2015), there were no interactions between terrain and cadence, which suggests, that the present findings would also apply to uphill cycling in laboratory and field conditions.